2020
DOI: 10.3390/ma13214937
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Carbon Reinforced Concrete—Part 2: Discussion of Evaluation Concepts and Modelling

Abstract: Possible threats on the environment and human health by the leaching of new building materials and composites in contact to water should be prevented from the outset. It is therefore necessary to assess and ensure their environmental compatibility. For irrigated construction elements this is a challenging task, as there is no general correlation between known testing methods and outdoor emissions. A feasible assessment concept is needed for these conditions. In this work the German assessment method for perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In fact, façade panels, renders and coatings are exposed to dynamic weather conditions in contrast to constant conditions in the laboratory. For the leaching behaviour of inorganic constituents from concrete, plasters and renders, the DSLT does not necessarily deliver higher release compared with the field [42,43]. Figure 3 demonstrates the differences for arsenic, zinc and vanadium from concrete sheets tested in the laboratory and outdoors.…”
Section: Input For Estimation Of Emission Using Leaching Modelsmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, façade panels, renders and coatings are exposed to dynamic weather conditions in contrast to constant conditions in the laboratory. For the leaching behaviour of inorganic constituents from concrete, plasters and renders, the DSLT does not necessarily deliver higher release compared with the field [42,43]. Figure 3 demonstrates the differences for arsenic, zinc and vanadium from concrete sheets tested in the laboratory and outdoors.…”
Section: Input For Estimation Of Emission Using Leaching Modelsmentioning
confidence: 96%
“…A transfer of the derived functions to substances with similar leaching behaviour was successfully conducted by varying a constant in the regression term. Yet, the functions are to be verified by further tests, and a method to determine the constant on a laboratory scale should be developed [43].…”
Section: Source Part Of the Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Weiler et al studied the leaching behavior of irrigated building structures made of carbon-reinforced concrete with accelerated simulations at a laboratory scale [ 4 ]. Evaluation concepts are discussed in the second part of the work [ 5 ] to align simulation results to field conditions and enable the establishment of threshold values.…”
mentioning
confidence: 99%
“…Leaching tests represent a common thread in the submissions to this Special Issue [ 3 , 4 , 5 , 6 , 13 , 14 , 15 , 16 ]. The underlying mass transfer principles of column leaching tests are discussed by Liu et al [ 14 ], and Sakanakura et al [ 15 ] showed that adsorption parameters can be determined in batch leaching tests with varying liquid–solid ratios.…”
mentioning
confidence: 99%